Schiff base‐nickel, palladium, and platinum complexes derived from N‐cyclohexyl hydrazine carbothioamide and 3‐hydroxy‐4‐methoxybenzaldehyde: Selective antiproliferative and proapoptotic effects against colorectal carcinoma. Issue 6 (19th June 2019) - Arafath, Md. Azharul; Al‐Suede, Fouad S. R.; Adam, Farook; Al‐Juaid, Salih; Khadeer Ahamed, Mohamed B.; Majid, Amin M. S. A.
Abstract: The bidentate N ‐cyclohexyl‐2‐(3‐hydroxy‐4‐methoxybenzylidene)hydrazine‐1‐carbothioamide Schiff base ligand (HL) was coordinated to divalent nickel, palladium and platinum ions to form square planar complexes. The nickel and palladium complexes, [NiL2 ], [PdL2 ] form square planar complexes with 2:1 ligand to metal ratio. The platinum complex, [PtL(dmso)Cl] formed a square planar complex with 1:1 ligand to metal ratio. Platinum undergoes in situ reaction with DMSO before complexing with the ligand in solution. The cytotoxicity of HL, [NiL2 ], [PdL2 ], and [PtL(dmso)Cl] were evaluated against human colon cancer cell line (HCT‐116), human cervical cancer (Hela) cell line, melanoma (B16F10) cells, and human normal endothelial cell lines (Eahy926) by MTT assay. The [NiL2 ] complex displayed selective cytotoxic effect against the HCT 116 cancer cell line with IC50 of 7.9 ± 0.2 μM. However, HL, [PdL2 ], and [PtL(dmso)Cl] only exhibited moderate cytotoxic activity with IC50 = 75.9 ± 2.4, 100.0 ± 1.8, and 101.0 ± 3.6 μM, respectively. The potent cytotoxicity of [NiL2 ] was characterized using Hoechst and Rhodamine assays. The nickel complex, [NiL2 ], caused remarkable nuclear condensation and reduction in mitochondrial membrane potential. In addition, molecular docking studies confirms that [NiL2 ] possesses significant binding efficiency with Tyrosine kinase. Altogether, the results revealed that [NiL2 ] exhibits cytotoxicity against the cancer cells via Tyrosine kinase‐induced proapoptosis pathway. This study demonstrates that the [NiL2 ] complex could be a promising therapeutic agent against colorectal carcinoma. Abstract :